In vitro experiments of cerebral blood flow during aspiration thrombectomy: potential effects on cerebral perfusion pressure and collateral flow. (28th August 2015) - Lally, Frank; Soorani, Mitra; Woo, Timothy; Nayak, Sanjeev; Jadun, Changez; Yang, Ying; McCrudden, John; Naire, Shailesh; Grunwald, Iris; Roffe, Christine
Abstract : Background: Mechanical thrombectomy with stent retriever devices is associated with significantly better outcomes than thrombolysis alone in the treatment of acute ischemic stroke. Thrombus aspiration achieves high patency rates, but clinical outcomes are variable. The aim of this study was to examine the effect of different suction conditions on perfusate flow during aspiration thrombectomy. Methods: A computational fluid dynamics model of an aspiration device within a patent and occluded blood vessel was used to simulate flow characteristics using fluid flow solver software. A physical particulate flow model of a patent vessel and a vessel occluded by thrombus was then used to visualize flow direction and measure flow rates with the aspiration catheter placed 1–10 mm proximal of the thrombus, and recorded on video. Results: The mathematical model predicted that, in a patent vessel, perfusate is drawn from upstream of the catheter tip while, in an occluded system, perfusate is drawn from the vessel proximal to the device tip with no traction on the occlusion distal of the tip. The in vitro experiments confirmed the predictions of this model. In the occluded vessel aspiration had no effect on the thrombus unless the tip of the catheter was in direct contact with the thrombus. Conclusions: These experiments suggest that aspiration is only effective if the catheter tip is in direct contact with the thrombus. If the catheter tip is not in contact with the thrombus, aspirate is drawn from the vessels proximal of the occlusion. This could affect collateral flow in vivo.